2007
DOI: 10.1111/j.1532-5415.2007.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health and Cognitive Impairment in an English National Survey Population

Abstract: Poor dentition is associated with cognitive impairment. Nutritional status in people with cognitive impairment is recognized to be at risk. Although dental health did not account for the association between cognitive impairment and low BMI in this sample, other possible nutritional consequences require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 25 publications
10
69
1
2
Order By: Relevance
“…Several studies with different designs showed that tooth loss was associated with dementia and AD [53]. For example analysis of data coming from "2000 Health Survey for England" showed that loss of teeth was associated with cognitive impairment [119]. Similar results were obtained by Kim that studied the dental health in a Korean population [51].…”
Section: Association Between Periodontal Disease and Progression Of Asupporting
confidence: 68%
See 1 more Smart Citation
“…Several studies with different designs showed that tooth loss was associated with dementia and AD [53]. For example analysis of data coming from "2000 Health Survey for England" showed that loss of teeth was associated with cognitive impairment [119]. Similar results were obtained by Kim that studied the dental health in a Korean population [51].…”
Section: Association Between Periodontal Disease and Progression Of Asupporting
confidence: 68%
“…Clinical studies consistently show an association between tooth loss and AD/dementia [118,119]. In addition to PD, caries (tooth decay) and endodontic com-plications are significant causes of tooth loss and the possibility that these oral infections may contribute to AD pathogenesis cannot be excluded.…”
Section: Association Between Periodontal Disease and Progression Of Amentioning
confidence: 99%
“…[14] Cognitive impairment was defined on the basis of three or more incorrect responses out of 10. Such a cut-point has been used in previous studies and is a sensitive and specific marker of cognitive impairment [15][16][17]. The AMT is also highly correlated with the MMSE [18].…”
Section: Cognitive Impairmentmentioning
confidence: 97%
“…They not only have a lower number of natural teeth, but also present with a higher prevalence and incidence of caries and with more untreated lesions than their cognitively healthy peers [46][47][48][49][50] . The presence of natural teeth in humans seems related to better cognitive functioning, with several plausible explanations for this correlation have been proposed 51 .…”
Section: Cognitionmentioning
confidence: 99%